New COVID-19 Variants (IntechOpen, 2024)
New COVID-19 Variants - Diagnosis and Management in the Post-Pandemic Era provides a comprehensive overview of COVID-19, focusing on new variants and their diagnosis, treatment, and prevention. Due to the emergence of new viral variants, cases of COVID-19 are expected to increase. Thus, it is vital to take the necessary precautions to protect society and its most vulnerable members like the elderly and immunocompromised. This book discusses protective measures such as social distancing, mask mandates, vaccinations, and more.